THE PROSPECTS OF DEVELOPING THE DISTANCE EMPLOYMENT UNDER THE CONDITIONS OF CORONOMICS IN GEORGIA (Globalization and Business, 2023)
In the era of current globalization, when the whole world is faced with the qualitatively new economic crisis, for the purpose of raising the living standards of population the great importance is attached to ensuring their effective employment. The latter belongs to the major social-economic issues and poses quite a serious challenge to a country. The aforesaid is also conditioned by the fact that at the current stage of formation and operation of labour market the unemployment is regarded as the key factor causing poverty. Under the conditions of economics, the problem is more exacerbated by thousands of workplaces having been temporarily suspended and lost due to the spread of Covid19 within the country.  In such a situation it would be difficult to cope with the unemployment and make progress in effective employment without developing the socio-labour relations and applying its qualitatively new forms. Occasioned by the above mentioned, the paper aims at the profound study of peculiarities of the forms of distance employment, which are widespread in the international practice, and focuses on the formulation of certain directions and recommendations relating to the potential and prospects of their utilization in the country. In particular, on the basis of the research and analysis conducted the following key recommendations and conclusions have been reached:In the contemporary world the expansion of non-standard employment including the distance employment has radically changed the tendencies of developing the labour market. The mentioned forms of employment are characterized by: labour flexibility; the application of non-standard organizational-legal forms of labour; the adaptation of employers and employees to the constantly changing economic conditions; the realization of their interests, etc.;In the developed countries the distance employment greatly contributes to the increase in the overall level and scales of employment. Its main distinctive mark is the existence of workplaces out of enterprise (outworks). Accordingly, the distance employment is examined in the context of non-standard employment represented as the form of long-term labour relations with a single employer, which diverges from the standard model of full, regulated and open employment according to one or several criteria (performance, labour regime, labour hours, working conditions, work outcomes, working hours, work place and its location, social protection, the correlation between the subjects of labour relations, etc.);Based on its attractiveness as well as by popular demand, the distance employment is recently developing and enhancing at a fast pace all over the world. For instance, while at the outset of the 2000s approximately 30.0 million people were employed on distance jobs in the USA and EU countries, in the second decade of XXI century their number increased to 55.0 – 60.0 million. The quantity of distance employers is annually growing by 20%-30% worldwide. In 2019, the number of outworking employees equaled to 39.0% all over the world. In addition, 28% more of employees had the right to distance jobs. The USA, Canada, Finland, Denmark and Sweden lead this sphere;The advantages of distance employment are as follows: 1. On behalf of employees: flexible working hours; the standard, comfortable conditions of employment; the opportunity to get education and participate in the socially useful activities; extra income; contracts with outer organizations; the possibility to schedule the working time and the labour optimization;  the provision of high efficiency and quality of work; the maintenance of the personal rhythm, resting  and working time and their protection; saving of expenses; the decrease in time of communications; comfortable working space;  the lack of corporate culture;  the distance employment is the basis of creative self-realization, pleasure and satisfaction for a number of employers. 2.On behalf of employers: employing the professionals and providing the flexibility of personnel; raising the labour productivity and efficiency; ensuring the personnel loyalty; providing the clients with round –the-clock information services; forming the flexible organizational structure for enterprises; work site arrangement, saving rental costs. 3. On behalf of a state:  the increase in the level of employment and the decrease in the level of unemployment; the development of distance employment involving the disabled persons; the decrease in traffic in the country; the increase in the number of economically active population; scaling down the migration;Apart from the positive points, the expansion of distance employment is related to the significant risk factors, which necessitate the introduction of their controlling mechanism by the state. It should be focused on reducing the aforesaid risk-factors to minimum level and protecting social and legal rights of employees;Occasioned by the goals of ensuring the  effective employment as well as according to National Strategy for Labour Market and Employment Policy of Georgia 2019-2023, the provision of  developing the non-standard forms of employment assumes the great importance in the country. It is also essential to regularly conduct the impact assessment defining the scales of distance jobs and the pace of their expansion at the level of total employment;In order to conduct the comprehensive analysis and evaluation of distance employment at the overall level of employment, we deem it expedient to make its classification not in terms of the scope of  fields but according to the professions, which are currently  singled out as being in great demand.  Currently, at the labour market of Georgia the following specialties are most demanded by employers: 1. A specialist in  marketing; 2. Sales manager; 3. The specialist in the area of internet-technologies; 4. A web-designer; 5. A programmer; 6. Distributer; 7. Tourism ( where the demands have, accordingly, increased on the specialties such as a waiter, a barman,  a hotel manager, a guide); 8. Audit; 9. Accountant – financier; 10. A doctor; 11. A lawyer; 12. A teacher; 13. A construction manager; 14. Translator, etc.  Exactly the mentioned professions are attractive in terms of developing the distance employment in a number of developed countries abroad;With the aim of raising the efficiency of state programs for employment and regulating the distance employment, the regular researches should be necessarily implemented in the direction of determining the real demands on working forces at the labour market. This is the only way offering the real prospects for developing the distance employment and their involvement in the state and regional programs of employment. The latter will considerably contribute to improving the quality of working life of population and ultimately, the raise of living standards.